Derivations of a Sullivan Model and the Rationalized G-Sequence - Oteng Maphane (International Journal of Mathematics and Mathematical Sciences)
Let Gk,nℂ for 2≤k<n denote the Grassmann manifold of k-dimensional vector subspaces of ℂn. In this paper, we compute, in terms of the Sullivan models, the rational evaluation subgroups and, more generally, the G-sequence of the inclusion G2,nℂ↣G2,n+rℂ for r≥1.